"The assessment really helps you with the first step in recovery." What do clients think substance use disorder treatment intake assessments should look like?. Issue 4 (2nd October 2021) - Treiman, Katherine; Padwa, Howard; Mark, Tami L.; Tzeng, Janice; Gilbert, Marylou
Abstract: Background: In general, research has found that patient-centered substance use disorder treatment is positively correlated with improved patient outcomes. However, little research has examined what factors make intake assessments—the first step in addiction treatment—patient-centered. Methods: We conducted interviews with 30 Medicaid-enrolled individuals who received addiction treatment in California about their experiences with the intake assessment process. Results: Participants reported that the intake assessment process evoked strong feelings, both positive and negative. Some participants said that answering detailed questions about their substance use, mental health, and social relationships, for example, was cathartic and gave them helpful insights. Other participants found the questions invasive, exhausting, and anxiety provoking. Participants also emphasized how critical it is for the person conducting the assessment to be supportive, nonjudgmental, and attentive. Participants recommended delaying the comprehensive assessment because they did not feel physically or emotionally ready to complete the intake. Conclusions and recommendations: Patients' introduction to addiction treatment is typically the intake assessment. By understanding how patients experience intake assessments, providers can make the process more patient-centered, which may lead to improved patient outcomes.